Effects of Use of Steel Fibres in Concrete Paving Blocks: Effects of Steel Fibres on the Performance of Concrete Paving Blocks (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Use of concrete paving blocks has increased in the areas where the normal flexible pavement does not last long. Application of concrete paving blocks is developing very fast for various reasons such as high resistance, to deformation, durability, easy and rapid quality construction, ability to carry traffic immediately after construction, compatibility with the environment and aesthetic features, etc. The structural behavior of CBP is similar to flexible pavement. However, the performance of CBP depends upon block shape, size, thickness, type of building and jointing stand, joint width. Block layout is also important, which affects the overall performance of CBP. The edge restraint is one of the features which are essential to stop mitigation of blocks outwards .The interlocking mechanism is one of the unique characteristic of the CBP. The performance of CBP largely depends on how well the interlock has achieved. The project deals with study of effects of steel fibres on concrete paving blocks. In many factories it is observed that there is no standard method used for manufacturing of paving block. In this project we use IS 156582006 code for design of concrete mix. In this project we investigate the effects of different test for compressive strength, flexural strength and tensile strength, behavior of mechanical and physical properties of FRC at various temperatures and investigation of reduction in cement content for different percentage addition of fibres in mix when permissible strength results are achieved.